A Systematic Review of External Validity in Pediatric Integrated Primary Care Trials. (10th September 2020) - Callejo-Black, Alicia; Wagner, David V; Ramanujam, Krishnapriya; Manabat, Ann Jeline; Mastel, Sarah; Riley, Andrew R
Abstract: Objective: We used the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework to conduct a systematic review of external validity reporting in integrated primary care (IPC) interventions for mental health concerns. Methods: We searched Medline, CINAHL, PsycINFO, the Cochrane Center Register of Controlled Trials, and relevant literature to identify publications from 1998 to 2018 reporting on open, randomized, or quasi-randomized trials of IPC interventions that targeted child (ages 0–18 years) psychological symptoms. For each publication, we extracted the information reported in each RE-AIM domain and calculated the proportion of the total studies reviewed. Results: Thirty-nine publications describing 25 studies were included in the review. Publications rarely reported some indicators of external validity, including the representativeness of participants (12%), rate of adoption clinics or providers (16%), cost of implementation (8%), or evidence of maintenance (16%). Few studies reported on key pragmatic factors such as cost or organizational change processes related to implementation and maintenance. Strengths of some studies included comparisons of multiple active treatments, use of tailorable interventions, and implementation in "real world" settings. Conclusions: Although IPC interventions appear efficacious under research conditions, there are significant knowledge gaps regarding the degree to which they reach and engage target recipients, what factors impact adoption and implementation of IPC interventions by clinicians, how fidelity can be maintained over time, and cost-effectiveness. Pediatric IPC researchers should embrace dissemination and implementation science methods to balance internal and external validity concerns moving forward.